(untitled) (Boston, 2002)
The american tradition in literature will find its distinctive qualities of selection and scholarship continued and enhanced. Manintaining that necessary core, we have responded to changing pedagogic climates and have taken advantage of improved book-making technologies and advances in electronic support systems to incorporate a number of major innovations.
Keywords: American literature